How to increase efficiency of governance management? - Kovalev, Mikhail M.; Avdonin, Alexei A. (Journal of the Belarusian State University. Economics, 2021)
A brief analysis of the state of the public sector of the Belarusian economy is presented. The main problems and directions of creating an open system for managing state assets are highlighted which may be useful to the developers of the law about state organizations and economic entities with the participation of the state.